Socialization of the Implementation of Pregnancy Exercises to Deal with the Childbirth Process - Khusnul Nikmah; Lilik Darwati; Syaibah Faiqotul Hikmah (Journal of Community Engagement in Health, 2025)
Pregnancy exercise is an exercise program for pregnant women to prepare the mother's physical condition to maintain the condition of the muscles and joints which play a role in the birthing process. The benefits of regular pregnancy exercise are very helpful in maintaining health and smooth delivery and postpartum processes because pregnancy exercise will make the body flexible, especially the muscles of the birth canal. The purpose of this service is to find out whether pregnant women are ready to face the birth process well and smoothly. The method used is to provide counseling to all pregnant women who undergo pregnancy check-ups, then carry out direct pregnancy exercise practices, followed by a question and answer session and distribution of door prizes for pregnant women who ask questions. The questionnaire in the form of open questions with the results of increasing knowledge of pregnant women to do pregnancy exercises so that pregnant women are ready to face the labor process at TPMB Miftahul Khoiriyah, S.Keb. Bd. In this way, pregnant women have awareness of the importance of doing exercise to make it a necessity for pregnant women so that pregnant women can do pregnancy exercise regularly and independently at home.